2014
DOI: 10.1097/01.meg.0000435546.87251.f7
|View full text |Cite
|
Sign up to set email alerts
|

A UK study assessing the population prevalence of self-reported gluten sensitivity and referral characteristics to secondary care

Abstract: GS is commonly self-reported with symptoms suggesting an association with irritable bowel syndrome. The majority of patients have NCGS, an entity which demonstrates clinical and immunologic difference to CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
178
6
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(214 citation statements)
references
References 31 publications
19
178
6
11
Order By: Relevance
“…Furthermore, gluten-sensitive individuals referred to secondary care are predominantly female, report an association with IBS, and experience intestinal and extraintestinal symptoms after gluten ingestion. Moreover, patients in secondary care with self-reported gluten sensitivity were similar to individuals reporting gluten sensitivity within the population cohort [13].…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, gluten-sensitive individuals referred to secondary care are predominantly female, report an association with IBS, and experience intestinal and extraintestinal symptoms after gluten ingestion. Moreover, patients in secondary care with self-reported gluten sensitivity were similar to individuals reporting gluten sensitivity within the population cohort [13].…”
mentioning
confidence: 61%
“…In New Zealand, CD affects 1 % of children, yet 5 % report gluten avoidance [12]. Most recently, we have reported that in a large population (n = 1,002) living in the United Kingdom, sensitivity to gluten-based products is self-reported by 13 % of the population, with 3.7 % consuming a GFD, even though only 0.8 % are aware that they have been formally diagnosed with CD [13]. Furthermore, gluten-sensitive individuals referred to secondary care are predominantly female, report an association with IBS, and experience intestinal and extraintestinal symptoms after gluten ingestion.…”
mentioning
confidence: 99%
“…Finally, Aziz et al [16] on a population of 1,002 adults describe a self-reported prevalence for NCGS of 13 % (female 79 %) with 3.7 % consuming a gluten-free diet and 0.8 % known to have a doctor diagnosis of CD; individuals with NCGS had an increased prevalence of fulfilling the Rome III criteria for IBS, in comparison with those without NCGS.…”
Section: Epidemiologymentioning
confidence: 99%
“…skrywać się pod maską padaczki opornej na leczenie farmakologiczne [12]. NCNG u osób dorosłych występuje wielokrotnie częściej u płci żeńskiej [11,13], natomiast na podstawie jeszcze nielicznych publikacji i obserwacji własnych można wnioskować o przewadze płci mę-skiej w pediatrycznej grupie wiekowej [10,14]. Początko-wo szacowano częstość NCNG na ponad 5% ogólnej populacji [2].…”
Section: Rozpoznawanie I Epidemiologia Ncngunclassified
“…Niestety uwaga badaczy skupia się głównie na poznawaniu różnic między celiakią i nadwrażliwością na gluten, a pomijany jest brak homogenności pacjentów z NCNG [17,18]. Aktualnie dominuje pogląd, że NCNG różni od celiakii niewspółwystępowanie z chorobami autoimmunologicznymi [13,20]. Niektóre prace kazuistyczne wydają się jednak wskazywać, że można będzie wyróżnić postaci NCNG charakteryzujące się patofizjologią warunkującą powiązanie z zaburzeniami autoimmunologicznymi [19].…”
Section: Ncng -Choroba Czy Zespół Chorób?unclassified